Population genetics analysis of Tolai hares (Lepus tolai) in Xinjiang, China using genome-wide SNPs from SLAF-seq and mitochondrial markers - Mamat, Miregul; Shan, Wenjuan; Dong, Pengcheng; Zhou, Shiyu; Liu, Peng; Meng, Yang; Nie, Wenyue; Teng, Peichen; Zhang, Yucong (Frontiers in Genetics, 2023)
The main topic of population genetics and evolutionary biology is the influence of the ecological environment, geographical isolation, and climatic factors on population structure and history. Here, we estimated the genetic diversity, genetic structure, and demographic history of two subspecies of Tolai hares (Lepus tolai Pallas, 1778), L. t. lehmanni inhabiting Northern and Northwest Xinjiang and L. t. centrasiaticus inhabiting Central and Eastern Xinjiang using SNP of specific-length amplified fragment sequencing (SLAF-seq) and 4 mitochondrial DNA (mtDNA). Our results showed a relatively high degree of genetic diversity for Tolai hares, and the diversity of L. t. lehmanni was slightly higher than that of L. t. centrasiaticus, likely due to the more favorable ecological environment, such as woodlands and plains. Phylogenetic analysis from SNP and mtDNA indicated a rough phylogeographical distribution pattern among Tolai hares. Strong differentiation was found between the two subspecies and the two geographical groups in L. t. centrasiaticus, possibly due to the geographical isolation of mountains, basins, and deserts. However, gene flow was also detected between the two subspecies, which might be attributed to the Tianshan Corridor and the strong migration ability of hares. Tolai hare population differentiation occurred at approximately 1.2377 MYA. Population history analysis based on SNP and mtDNA showed that the Tolai hare population has a complex history and L. t. lehmanni was less affected by the glacial event, possibly because its geographic location and terrain conditions weaken the drastic climate fluctuations. In conclusion, our results indicated that the joint effect of ecological environment, geographic events, and climatic factors might play important roles in the evolutionary process of L. t. lehmanni and L. t. centrasiaticus, thus resulting in differentiation, gene exchange, and different population history.